Rethinking agency—The 2022 agenda for the systems community. (24th November 2021) - Klein, Louis; Buckle, Pamela; Nguyen, Nam; Preiser, Rika; Ison, Ray
Abstract: Five clusters of concern arising from IFSR‐facilitated conversations with its organisational members are used to invite the broader systems community to rethink agency. It is argued that by addressing the cluster elements, potential will be co‐created for the systems community as a whole to help citizens venture beyond failing responses to the global problematique and the Anthropocene‐creating thinking in which we humans are trapped. The five clusters are as follows: Exploring the in‐between : Growing a shared understanding is going beyond a competition of ideas or a clash of concepts. It is a joint exploration of the unknown in‐between. Including the excluded : Systems research happens in open research ecosystems, not in disciplinary silos. It is transdisciplinary and constitutes a global discourse. Living questions : Questions shape paradigms. Transcending paradigms starts from allowing the questions to have their own life, to grow and to dissolve, to improve and to transform. Going beyond systems literacy : Learning to speak systems is one thing, proficiency in systems thinking, systems doing and systems being another. There is a difference between knowing and understanding that we may address as systems wisdom. Rethinking agency : Agency goes from ego to eco, from me to we. Yet, it is not an either–or; it is ego and eco, me and we. To understand agency, we need to understand the 'and'.